Ophtalmological Changes in Prader-Willi Syndrome: Case Report - Osório Tavares, Mónica (2022)
This work reports a case of Prader-Willi syndrome, with dyschromatopsia, its clinical characteristics and ophthalmological changes, monitoring and treatment, in a 6-year-old child. Prader-Willi syndrome is rare, being an autosomal dominant disorder caused by the exclusion of the proximal long arm of the paternal chromosome 15 (15q11-q13) or inheritance of both pairs of chromosomes 15 from the mother. Clinical manifestations include mental retardation; muscle hypotonia; hyperphagia; obesity; low; hypogonadism; strabismus; and hypersomnolence. Ophthalmological manifestations included: almond-shaped eyes, a characteristic of the syndrome, convergent strabismus, hyperopia and a dyschromatopsia. Prescribed optical correction and orthoptic treatment with occlusion and improvement of ocular deviation. After an extensive review of the literature, we found no reference to other cases of dyschromatopsia related to Prader-Willi syndrome. It evidenced the need for revision in the administration of the Brazilian public health system, highlighting the long itinerary for diagnosis and treatment covered by the patient. as well as the possibility of being assisted by telemedicine.